¡Zapatero a sus zapatos! La no interferencia del Poder Judicial sobre las actuaciones arbitrales en Perú - Taboada Mier, Jose Carlos (Pontificia Universidad Católica del Perú, 2025)
The principle of judicial non-interference in arbitration constitutes an essential safeguard to protect party autonomy and the effectiveness of arbitral proceedings. Its origin is linked to the nature of arbitration according to its historical background, including its materialization in the New York Convention and the UNCITRAL Model Law, instruments that inspired Peruvian legislation. This principle prevents the Judiciary from intervening during the development of arbitration, except in expressly regulated cases, such as assistance in evidence-taking or the enforcement of interim measures. Doctrine and the Constitutional Court’s jurisprudence have reaffirmed that judicial control must remain residual, exercised only through annulment or constitutional actions. In this way, non-interference ensures that the arbitration agreement retains its meaning, strengthening confidence in this mechanism of dispute resolution.

El principio de no interferencia judicial en el arbitraje constituye una garantía esencial para salvaguardar la autonomía de las partes y la eficacia del proceso arbitral. Su origen se vincula con la naturaleza del arbitraje según sus antecedentes históricos, incluyendo su materialización en la Convención de Nueva York y la Ley Modelo de la CNUDMI, instrumentos que inspiraron la legislación peruana. Este principio impide que el Poder Judicial intervenga durante el desarrollo del arbitraje, salvo en casos expresamente previstos, como la asistencia en la producción de pruebas o la ejecución de medidas cautelares. La doctrina y la jurisprudencia del Tribunal Constitucional han reafirmado que el control judicial debe ser residual, ejercido únicamente a través de la anulación o el amparo. Así, la no interferencia asegura que el pacto arbitral conserve sentido, fortaleciendo la confianza en este mecanismo de resolución de controversias.
The Non-Interference of the Judiciary in Arbitral Proceedings in Peru
Keywords: Party agreement; Non-intervention; Judicial control; Acuerdo de partes; No intervención; Control judicial; https://purl.org/pe-repo/ocde/ford#5.05.00